Accuracy of Dental and Chronological Age Estimation in A Sample Turkish Caucasion Children: Comparison of Demirjian’s and Willems Methods - NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2023)
Objective: The purpose of this study is to apply Demirjian’s and Willems’ methodologies and to define whether there are any discrepancies in predicting dental age versus chronological age in a sample Turkish Caucasian children. Methods: A total of 150 Turkish Caucasian children with known chronological age and gender were chosen. The chronological age was determined by subtracting the date of birth from the date of the radiograph, and it was expressed as a number with two decimal places. Each age group was determined to have a minimum sample size of 12 and a maximum sample size of 27. All panoramic radiographs were scored according to the criteria of Demirjian’s and Willems methodologies with Onyx Ceph 3.1.54 software. Results: The dental ages of the cases ranged from 4.82 to 15.66 years calculated by the Demirjian’s method, with an average of 9.47±2.27 years, while the Willems method of the cases ranged from 4.13 to 14.34 years calculated by the Demirjian’s method, with an average of 8.87±2.24 years. According to Demirjian’s method, in the developmental evaluation of dental age, 45.3% of boys were found to have a statistically higher chronological age than girls (p<.05), while no statistically significant difference was found between dental age and chronological age in developmental evaluation according to Willems method (p>.05). Conclusion: The Willems method was shown to be more accurate in determining dental age in Turkish children. Further studies on large population groups and diverse ethnicities are required to increase the reliability and repeatability of the results. Keywords: Dental age, chronological age, Demirjian’s method, Willems method
Keywords: Diş Hekimliği; Klinik Bilimler; Oral Diagnoz ve Radyoloji; Sağlık Bilimleri; Dentistry; Clinical Sciences; Oral Diagnosis and Radiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry